Examining market efficiency and integration of the Islamic stock indices / Noryati Ahmad. - Ahmad, Noryati (Universiti Teknologi Mara Selangor, 2016)
The question of whether the stock market is efficient has been an ongoing debate among researchers. Generally, empirical evidence indicates that most conventional stock indices for developed countries are weak form efficient while inconclusive results are discovered for developing countries. With the growing importance of the Islamic capital markets that run parallel to the conventional stock markets, similar question arises as to whether these new Islamic capital markets are also efficient. Hence this paper aims to examine the weak form efficiency of the Islamic stock indices. Autocorrelation Function (ACF) test and Variance Ratio (VR) test are used to test the market efficiency of the Islamic stock indices from China, India, South Africa, Malaysia, Dubai, Qatar and Japan. The study uses daily data covering the year 2008 until 2012. In addition, this paper attempts to unveil the dynamic causal relationships among the Islamic capital markets. Bivariate Granger Causality test is employed to achieve the objectives. Interestingly only the Islamic stock indices for Malaysia and India are weak form efficient while the results of the Islamic stock indices for Qatar and Kuwait are not. The results of the other Islamic stock indices studied are inconclusive. Johansen multivariate cointegration tests reveal no long-term relationship among the Islamic stock indices. On the other hand, bivariate Granger Causality tests report short run co-movements between Islamic stock indices of Muslim countries and non-Muslim countries, an indication of growing interest of the Islamic financial markets among investors.